The Role of Traditional Leaders in Local Governance: A Case Study of Jambi Province, Indonesia - H. M. Chotib (Enigma in Cultural, 2024)
Indonesia's decentralized governance system provides space for the integration of traditional leadership into local administration. This study examines the role of traditional leaders in local governance within Jambi Province, Indonesia, investigating their interactions with the formal public administration system, influence on policy implementation, and contribution to community development. This qualitative study employed a case study approach focusing on three districts in Jambi Province with varying degrees of adherence to traditional customs. Data collection involved semi-structured interviews with traditional leaders, government officials, and community members. Archival research, including local regulations and policy documents, supplemented the primary data. Thematic analysis was used to identify key themes and patterns. Traditional leaders in Jambi continue to hold significant influence in local communities, particularly in rural areas. Their roles encompass conflict resolution, cultural preservation, and advocacy for community interests. While their authority is not formally recognized within the modern administrative structure, they play a crucial role in mediating between communities and the government. The study found varying degrees of collaboration and tension between traditional leaders and government officials, depending on factors such as the leaders' individual personalities, the prevailing cultural norms of the community, and the specific policy area in question. The findings highlight the complexities of integrating traditional leadership into modern governance systems. While traditional leaders can contribute valuable local knowledge and legitimacy, their involvement can also pose challenges to bureaucratic procedures and accountability mechanisms. The study underscores the importance of recognizing and accommodating traditional authority while ensuring transparency and adherence to democratic principles.